Effect of tillage method and weeding regime on soil weed seed bank status and yield performance of wheat (Progressive Agriculture, 2016)
An experiment was conducted at the Agronomy Field Laboratory and net house of the Department of Agronomy, Bangladesh Agricultural University, Mymensingh from November 2012 to March 2014. Wheat (cv. BARI Gom-26) was sown with two tillage methods viz., (i) conventional tillage and (ii) stale seedbed technique and nine weeding regimes viz., (i) Unweeded (Control), (ii) Weed free, (iii) Hand weeding (HW) at 15 Days after sowing (DAS), (iv) HW at 15 and 45 DAS, (v)   HW at 25 and 45 DAS (vi) HW at 25 DAS (vii) HW at 25 and 60 DAS (viii) 2,4-D amine at 15 DAS and (ix) 2,4-D amine at 15 DAS + HW at 60 DAS. The design was split-plot with three replications where tillage method was assigned to the main plots and weeding regime to the sub plots. Conventionally tilled plots were infested with 12 weed species of which the five most dominant weed species in descent order were Polygonum coccineum L, Chenopodium album L, Cynodon dactylon L., Sonchus arvensis L. and Cyperus rotundus L. In stale seedbed out of 15 weed species Digitaria sanguinalis L. and Hedyotis corymbosa (L.) Lamk. was dominant instead of Chenopodium album L. and Sonchus arvensis L. identified in conventional tillage. In soil weed seed bank study, 28 species were identified in conventional tillage and 30 in stale seedbed. Among them annuals were dominant over perennials and broadleaves over grasses and sedges. In conventional tillage, the five most dominant weed species in descent order were Chenopodium album L., Hedyotis corymbosa L., Sonchus arvensis L., Polygonum coccineum L. and Rotala ramosior L. while in stale seedbed, five dominant weeds were Polygonum coccineum L., Chenopodium album L., Cynodon dactylon L., Lindernia procumbens Krock. and L. hyssopifolia L. Except the number of spikelets spike-1, rest of all other yield attributes and yield of wheat were affected significantly by the tillage methods. Stale seedbed technique yielded the higher grain (3.54 t ha-1) and the conventional tillage yielded the lower (3.13 t ha-1). The effect of weeding regime was significant on wheat except plant height and 1000-grain weight. The highest grain yield (3.85 t ha-1) was recorded from weed free treatment followed by 2,4-D amine at 15 DAS and lowest (3.22 t ha-1) from control. Interaction between the treatments was also. The highest grain yield (4.09 t ha-1) was recorded from the stale seedbed technique kept weed free followed by 2,4-D amine at 15 DAS and lowest grain yield (3.04 t ha-1) recorded from the conventional tillage retained unweeded.Progressive Agriculture 27 (1): 9-19, 2016